The feasibility of pathogenetic therapy for chronic viral hepatitis C in adult HIV-infected patients - E. B. Bun'kova; N. A. Bileva; M. I. Sinel'nikov; A. E. Bilev (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2024)
In the third decade of the XXI century, HIV infection and viral hepatitis C remain urgent problems of modern medicine. Only in the Russian Federation in 2023, more than 1.6 million HIV-infected people and about 2 million patients with chronic viral hepatitis C are registered. Patients with a combined course of these diseases are of particular concern. However, insufficient coverage of etiotropic therapy for patients with chronic viral hepatitis C due to its high cost leaves pathogenetic therapy as the only available method of treatment for many of them. Material and Methods. Clinical data of patients hospitalized in the day hospital of the state budgetary health care institution "Samara Regional Clinical Center for AIDS Prevention and Control" were used. Physical, virological, immunological, biochemical and general clinical methods, elastometry of liver tissue were used for examination of hospitalized patients. Statistical processing of the results was performed using the application program "Statgrarhics Plus for Windows". Pathogenetic therapy was carried out in a two-week course in accordance with the "Recommendations for the diagnosis and treatment of adult patients with hepatitis C" (2013) and included (along with protective regime and therapeutic nutrition) the use of detoxification and metabolic therapy. Antiretroviral therapy with 3–4 drugs was carried out in 68% of the patients. Results. It was shown that the prescribed course of pathogenetic therapy of chronic viral hepatitis C did not have the expected effectiveness in the majority of patients referred for treatment according to the dynamics of changes in the values of "liver tests", despite the fact that the "right subcostal syndrome" was eliminated in 75.7% of persons with stage 3 and 66.7% with stages 4A and 4B of HIV infection. Statistical studies of the relationship (linear, rank and canonical) did not reveal its presence between the results of the conducted treatment and the complex of initial clinical and clinicallaboratory data obtained during hospitalization of the examined persons. Discussion. The presence of cytolysis syndrome and "right subcostal syndrome" is not a valid criterion for referral to a two-week course of pathogenetic therapy of chronic viral hepatitis C in order to obtain a positive result in the majority of patients with stages 3, 4A and 4B of HIV infection. Other baseline data (virologic and immunologic indices, degree of liver tissue fibrosis, indices of general and biochemical blood analysis) had no reliable correlation with the results of treatment, which did not allow their use for predicting the effectiveness of the prescribed treatment. Antiretroviral therapy was not associated with the results of pathogenetic therapy of chronic viral hepatitis C according to the indicators of cytolysis syndrome and "right subcostal syndrome", despite the fact that most of the prescribed drugs had a hepatotoxic effect.